2004
DOI: 10.1016/j.ejcts.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature monitoring during cardiopulmonary bypass?do we undercool or overheat the brain?*1

Abstract: If brain venous outflow Tdegrees (JB) accurately reflects brain Tdegrees, NP Tdegrees is a safe surrogate indicator of cooling. During rewarming, all peripheral sites underestimate brain temperature and caution is required to avoid hyperthermic arterial inflow, which may inadvertently, result in brain hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The adequate temperature monitoring sites provide optimal estimation of intracerebral temperature [11]. T Naso reflects the carotid artery temperature, and is one of the most optimal surrogates of cerebral temperature because of the easy access and limited risk [12]. However, monitoring T Naso is unable to estimate left and right carotid artery temperature separately.…”
mentioning
confidence: 99%
“…The adequate temperature monitoring sites provide optimal estimation of intracerebral temperature [11]. T Naso reflects the carotid artery temperature, and is one of the most optimal surrogates of cerebral temperature because of the easy access and limited risk [12]. However, monitoring T Naso is unable to estimate left and right carotid artery temperature separately.…”
mentioning
confidence: 99%
“…Conventional monitoring sites may not reflect the core brain temperature. Kaukuntla et al compared jugular bulb venous temperatures during deep hypothermic circulatory arrest and normothermic bypass with nasopharyngeal, arterial inflow, oesophageal, venous return, bladder and orbital skin temperatures [75]. It was found that during rewarming, all peripheral sites underestimated brain temperature.…”
Section: Temperature Monitoring For Brain Coolingmentioning
confidence: 98%
“…Avoidance of cerebral hyperthermia in the setting of CPB has been promoted to avoid cerebral injury [10,12,[20][21][22]. Scheffer and Sanders [10] (2003) highlight that although the independent relationship between cerebral hyperthermia during CPB and neurologic injury has not been unequivocally proven, sufficient and compelling indirect evidence supports extreme caution.…”
Section: Avoidance Of Hyperthermiamentioning
confidence: 98%
“…In 2004, Kaukuntla and colleagues [12] demonstrated that commonly used core temperature monitoring sites (bladder, esophageal, and NP) were not accurate measures of cerebral temperature where JB temperature is used as the gold standard. The authors concluded that arterial outlet temperatures should be monitored to avoid cerebral hyperthermic inflow.…”
Section: Optimal Site For Temperature Measurementmentioning
confidence: 98%